A novel foaming approach to prepare porous superabsorbent poly(sodium acrylic acid) resins. Issue 3 (23rd August 2014) - Bao, Jianshe; Chen, Si; Wu, Bozhen; Ma, Meng; Shi, Yanqin; Wang, Xu
ABSTRACT A system composed of surfactant and foam stabilizer is used in preparing porous superabsorbent resins (SARs) of poly(sodium acrylic acid) (PAA‐Na), which is obtained by free‐radical solution polymerization of partially neutralized acrylic acid with mechanical agitation of eggbeater. Different types of surfactant, including anionic surfactant sodium n‐dodecyl benzene sulfate (SDBS), cationic surfactant cetyltrimethyl ammonium bromide, and nonionic surfactant alkylphenols poly(oxyethylene) (OP‐10), are used as blowing agent to produce pores by mechanical agitation, and triethanolamine (TEA) is used to act as foam stabilizer agent. The results show that a synergistic effect of SDBS with TEA is obtained and the packing density is decreased, which could be proved by the clearly porous morphology, and the water absorbing capacity of SARs is enhanced. As a result, such method can get PAA‐Na SARs without any organic solvents, which provides an environmentally beneficial way to prepare SARs for hygiene and biomedical products. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41298.